2008
DOI: 10.1016/j.jacc.2007.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Localized Elevation of Shear Stress Is Related to Coronary Plaque Rupture

Abstract: Although the absolute value of shear stress is not sufficient to directly provoke mechanical destruction of the fibrous cap, localized high shear stress might be a trigger of fibrous cap rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(78 citation statements)
references
References 39 publications
9
66
0
3
Order By: Relevance
“…22 • Increased postoperative procoagulants (fibrinogen, factor VIII coagulant, von Willebrand factor, ␣1-antitrypsin), increased platelet reactivity, 23 decreased endogenous anticoagulants (protein C, antithrombin III, ␣2-macroglobulin), 24 and decreased fibrinolysis 25 have been reported. However, postoperative hypercoagulability is notorious for its venous complications precipitated by stasis and immobilization, and reports of hypercoagulability and/or decreased fibrinolysis causing myocardial ischemia, 26,27 infarction, 28 or arterial bypass thrombosis 29 are scarce.…”
Section: Acute Coronary Syndrome (Type 1 Pmi)mentioning
confidence: 99%
See 1 more Smart Citation
“…22 • Increased postoperative procoagulants (fibrinogen, factor VIII coagulant, von Willebrand factor, ␣1-antitrypsin), increased platelet reactivity, 23 decreased endogenous anticoagulants (protein C, antithrombin III, ␣2-macroglobulin), 24 and decreased fibrinolysis 25 have been reported. However, postoperative hypercoagulability is notorious for its venous complications precipitated by stasis and immobilization, and reports of hypercoagulability and/or decreased fibrinolysis causing myocardial ischemia, 26,27 infarction, 28 or arterial bypass thrombosis 29 are scarce.…”
Section: Acute Coronary Syndrome (Type 1 Pmi)mentioning
confidence: 99%
“…Numerous studies 30 using perioperative Holter monitoring in high-cardiac-risk patients undergoing major surgery showed that silent, heart rate-related ST-segment depression is common postoperatively and is associated with in-hospital 22,31 and long-term morbidity and mortality. 32 Postoperative cardiac complications, including sudden death, 33,34 occurred after prolonged (Ͼ30 minutes, 35,36 Ͼ2 hours, 37,38 or Ͼ5 hours 39,40 ) silent ST-segment depression.…”
Section: Myocardial Oxygen Supply-demand Imbalance (Type 2 Pmi)mentioning
confidence: 99%
“…Significant work has been done, primarily in the coronary circulation, investigating the role of hemodynamic forces on atherosclerotic plaque stability. Shear stress [9,34] and blood pressure [8] have both been shown to relate to plaque stability and rupture. Conversely, plaque composition and topography can impact local stress concentrations and influence remodeling [15,28].…”
Section: Carotid Bifurcation Stenosis and Strokementioning
confidence: 99%
“…However, since the segmentation of the LV muscle mass from CT images was inevitable in the method, this method is applicable only to CT images with volumetric representation of the LV muscle layer. The method cannot be used in the other image modalities such as X-ray angiography, intravascular ultrasound (IVUS), and optical coherence tomography (OCT) [4,6,16,19].…”
Section: Introductionmentioning
confidence: 99%